2020
DOI: 10.1002/ppul.24660
|View full text |Cite
|
Sign up to set email alerts
|

Health system challenges for improved childhood pneumonia case management in Lagos and Jigawa, Nigeria

Abstract: This is the author manuscript accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…More than 70% of the facilities lacked health workers trained in IMCI and the IMCI booklets and algorithm charts for management of common childhood illnesses were also rare in these LLPHFs. This is comparable to another study carried out in Nigeria [ 51 ] and may explain the lack of good knowledge on management of these illnesses, exhibited in this survey especially among the lower professional cadres. This calls for training of health workers in LLPHF in IMCI and availing them with guidelines.…”
Section: Discussionsupporting
confidence: 88%
“…More than 70% of the facilities lacked health workers trained in IMCI and the IMCI booklets and algorithm charts for management of common childhood illnesses were also rare in these LLPHFs. This is comparable to another study carried out in Nigeria [ 51 ] and may explain the lack of good knowledge on management of these illnesses, exhibited in this survey especially among the lower professional cadres. This calls for training of health workers in LLPHF in IMCI and availing them with guidelines.…”
Section: Discussionsupporting
confidence: 88%
“…This is comparable to what other studies have described in Uganda [8,18,29], where most referrals from private clinics are sent to public hospitals. Most LLPHFs have minimum capacity with HWs who may have limited knowledge, inadequate infrastructure, lack of equipment and materials for managing critically ill children, such as oxygen, and often limited laboratory services as has been described in Nigeria [31]. To increase financial risk protection of households against impoverishment due to health expenditure, the Ugandan MoH planned on upgrading the status of all public HCII medical facilities to HCIII medical facilities and creating community hospitals [32].…”
Section: Discussionmentioning
confidence: 99%
“…From November 2018 to June 2019, we conducted a situational analysis of paediatric pneumonia in Lagos and Jigawa states of Nigeria, to inform the design of an intervention programme to reduce paediatric mortality. We found that while protective and preventive factors, such as vaccine coverage and clean cooking fuel, were high in Lagos, care-seeking and health facility service readiness were poor 3–6. Therefore, taking an approach that targets improved quality of care for pneumonia diagnosis and treatment could achieve mortality impact.…”
Section: Introductionmentioning
confidence: 92%
“…The WHO’s Integrated Management of Childhood Illness (IMCI) guidelines also recommend pulse oximetry for identifying severely ill patients with hypoxaemia in primary care settings, requiring referral to hospital 7–9. Despite their potential for reducing mortality, pulse oximeters are rarely available in frontline facilities in low-income and middle-income countries 6 10–12. Indeed, our survey of 58 Lagos health facilities in 2020 found pulse oximeters in none of the primary health facilities, 56% (15/27) of private health facilities and exclusively on the paediatric ward of three secondary health facilities 13…”
Section: Introductionmentioning
confidence: 95%